2005
DOI: 10.1677/joe.1.06142
|View full text |Cite
|
Sign up to set email alerts
|

Stress elevates corticotropin-releasing factor (CRF) and CRF-binding protein mRNA levels in rainbow trout (Oncorhynchus mykiss)

Abstract: The objectives of this study were to characterize rainbow trout (Oncorhynchus mykiss) corticotropin-releasing factor (CRF)-binding protein (CRF-BP) cDNA and to examine the variations in CRF-BP and CRF mRNA levels in response to different intensities of stress. Trout were physically disturbed by a single or three consecutive periods of chasing until exhaustion followed by 2 h of recovery. The pituitary CRF-BP and preoptic area CRF1 mRNA contents were significantly increased only after repeated chasing events. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 34 publications
9
33
1
1
Order By: Relevance
“…Interestingly, isolation, a stressor with significantly different attributes than either hypoxia or hyperammonemia, was also characterized by parallel increase in POA CRF and UI mRNA levels. In this case, however, as previously observed by Doyon et al (2005) for CRF, the isolation-induced increase in CRF and UI expression were sustained for the duration of the stressor. So while isolation may not pose a chronic threat to homeostasis and HPI axis activity habituation maybe relatively rapid, excitatory pathways involved in relaying the perceived psychological threat of the new environment maybe involved in keeping the CRF and UI mRNA levels elevated through at least 96 h. Similarly, isolation is known to result in a chronic reduction in food intake in rainbow trout (Overli et al 2002), a behavioral response that maybe at least partially mediated by the CRF-related peptides (Bernier 2006).…”
Section: Contrasting Effects Of Stressors On the Expression Of Crf Ansupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, isolation, a stressor with significantly different attributes than either hypoxia or hyperammonemia, was also characterized by parallel increase in POA CRF and UI mRNA levels. In this case, however, as previously observed by Doyon et al (2005) for CRF, the isolation-induced increase in CRF and UI expression were sustained for the duration of the stressor. So while isolation may not pose a chronic threat to homeostasis and HPI axis activity habituation maybe relatively rapid, excitatory pathways involved in relaying the perceived psychological threat of the new environment maybe involved in keeping the CRF and UI mRNA levels elevated through at least 96 h. Similarly, isolation is known to result in a chronic reduction in food intake in rainbow trout (Overli et al 2002), a behavioral response that maybe at least partially mediated by the CRF-related peptides (Bernier 2006).…”
Section: Contrasting Effects Of Stressors On the Expression Of Crf Ansupporting
confidence: 83%
“…Lastly, despite eliciting the most pronounced cortisol response among the challenges tested, subordination was only associated with an increase in CRF expression and not UI. Therefore, our results and those of Doyon et al (2003Doyon et al ( , 2005 suggest that the recruitment of POA CRF neurons is a nearly ubiquitous feature of the stress response in rainbow trout, as previously observed in the PVN of rats (Sawchenko et al 2000, Dayas et al 2001. In contrast, although the response may have been missed due to the limitations of our sampling regime, the recruitment of POA UI neurons appears to be stressor-specific and independent of the stress-induced cortisol response.…”
Section: Contrasting Effects Of Stressors On the Expression Of Crf Ansupporting
confidence: 82%
See 1 more Smart Citation
“…CRF also plays a role in suppressing reproduction and is involved in follicle maturation in the mammalian ovary (Nappi and Rivest, 1995;Asakura et al, 1997), which is consistent with our finding that the local CRF and CRF-R2 mRNA is expressed in the ovaries. Taken together, our data show that the molecular conservation of the CRF family is likely reflected in conserved functions based on its distribution in A. burtoni CRF systems are regulated by social stress During short-term physical stress, CRF mRNA and CRF-R1 mRNA levels increase in the mammalian hypothalamus or pituitary (Imaki et al, 1998;Qahwash et al, 2002;Doyon et al, 2005). In the teleost, CRF and CRFBP expression also increase in the hypothalamus, but CRF-R1 expression decreases in the pituitary during acute stress (Huising et al, 2004).…”
Section: Crf Systems Are Expressed In the Peripheral Tissuesmentioning
confidence: 63%
“…Studies on trout Doyon et al, 2005) reported that CRFBP may play a role in the inhibition of CRF signalling at its receptor in the acute stress response and this mechanism was confirmed by in vitro studies (Manuel et al, 2014). The effect of chronic stress in our study is in line with the findings of another experiment on rainbow trout (Jeffrey et al, 2012) where crfbp mRNA was unaffected by chronic stress caused by social interactions.…”
Section: Poamentioning
confidence: 86%